2014
DOI: 10.1186/1741-7015-12-46
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effectiveness and cost-effectiveness of antiretroviral therapy and pre-exposure prophylaxis for HIV prevention in South Africa

Abstract: BackgroundAntiretroviral therapy (ART) and oral pre-exposure prophylaxis (PrEP) are effective in reducing HIV transmission in heterosexual adults. The epidemiologic impact and cost-effectiveness of combined prevention approaches in resource-limited settings remain unclear.MethodsWe develop a dynamic mathematical model of the HIV epidemic in South Africa’s adult population. We assume ART reduces HIV transmission by 95% and PrEP by 60%. We model two ART strategies: scaling up access for those with CD4 counts ≤ 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
37
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 21 publications
3
37
0
1
Order By: Relevance
“…As a result, we cannot directly compare their findings to ours for age-prioritized PrEP under different modeling assumptions. Our data were also similar to those of Alistar et al [39], who predicted that unprioritized oral PrEP may cost $1172 per quality-adjusted life-year gained in South Africa whereas risk-prioritized PrEP was potentially cost-saving. Pretorius et al [40] predicted that 90% effective PrEP prioritized to South African women aged 25-35 years may cost over $20 000 per infection prevented over 10 years.…”
Section: Discussionsupporting
confidence: 78%
“…As a result, we cannot directly compare their findings to ours for age-prioritized PrEP under different modeling assumptions. Our data were also similar to those of Alistar et al [39], who predicted that unprioritized oral PrEP may cost $1172 per quality-adjusted life-year gained in South Africa whereas risk-prioritized PrEP was potentially cost-saving. Pretorius et al [40] predicted that 90% effective PrEP prioritized to South African women aged 25-35 years may cost over $20 000 per infection prevented over 10 years.…”
Section: Discussionsupporting
confidence: 78%
“…PO1 and PO2 are most cost-effective in Niger ($3.72 and $2.97 per DALY, respectively), the Democratic Republic of the Congo ($6.81 and $4.81 per DALY, respectively) and Ethiopia ($6.57 and $5.00 per DALY, respectively), partly driven by the comparatively lower costs of hospital care in those countries. For comparison, an insecticide-treated mosquito net (ITN) to prevent malaria is estimated to cost between $5 and $31 per DALY averted 19 , whereas HIV antiretroviral therapy has been estimated to cost upwards of $150 per DALY averted 20 . …”
Section: S57mentioning
confidence: 99%
“…Microbicide gels used by women on a per sex-act basis have one of the lowest reported ICERs with $297/DALY averted in South Africa, assuming 54% efficacy in HIV prevention and use in 72% of sex acts [47]. Another study examined both PrEP and ART scale-up; it suggests universal ART is the most cost-effective strategy and that oral PrEP with 60% efficacy provided to all HIV-uninfected adults in South Africa would provide few benefits beyond ART scale-up, but that PrEP focused to the highest risk individuals could be cost-saving compared to the status quo [48]. In serodiscordant couples, an estimated ICER for PrEP plus increased ART coverage in Uganda is $5,354/DALY averted [49], and in South Africa a similar intervention – with inclusion of ART initiation among eligible serodiscordant partners – has an ICER of $10,383/DALY averted [50].…”
Section: Hiv Prevention Interventionsmentioning
confidence: 99%
“…Importantly, these results excluded the costs of case identification and the frequent testing required to identify participants with high CD4 counts. Results of a different study implementing TasP for all HIV-infected adults in South Africa were also very cost-effective with an ICER between $160-$220/QALY gained and more favorable than providing PrEP to the HIV-negative population (also noted above) [48]. A study based in Uganda found expanding ART to 55% of serodiscordant couples resulted in an incremental cost per infection averted of $1,452 [49].…”
Section: Hiv Prevention Interventionsmentioning
confidence: 99%